Regulation of Autophagy under Stress (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Autophagy is a conserved degradative mechanism essential for cellular homeostasis in eukaryotic organisms. It is a cellular response mechanism that helps cells adapt and survive under various stressful conditions. It involves the degradation and recycling of cellular components to maintain cellular homeostasis and protect against damage from stressors like nutrient deprivation, oxidative stress, infection, and protein misfolding. However, the understanding of the molecular mechanisms of autophagy regulation is still in significant development, including the involvement of gasotransmitters and small signaling molecules, such as those produced under ROS, RNS and RSS. Dysregulation of autophagy has been implicated in various diseases, making it an important area of research to improve biomedical therapies and strategies for overcoming the challenges from environmental stresses. Therefore, this Special Issue aims to review the current developments regarding autophagy research.